Pivotal Role of Holes in Photocatalytic CO2 Reduction on TiO2. Issue 68 (24th November 2021) - Moustakas, Nikolaos G.; Lorenz, Felix; Dilla, Martin; Peppel, Tim; Strunk, Jennifer
Abstract: Evidence is provided that in a gas‐solid photocatalytic reaction the removal of photogenerated holes from a titania (TiO2 ) photocatalyst is always detrimental for photocatalytic CO2 reduction. The coupling of the reaction to a sacrificial oxidation reaction hinders or entirely prohibits the formation of CH4 as a reduction product. This agrees with earlier work in which the detrimental effect of oxygen‐evolving cocatalysts was demonstrated. Photocatalytic alcohol oxidation or even overall water splitting proceeds in these reaction systems, but carbon‐containing products from CO2 reduction are no longer observed. H2 addition is also detrimental, either because it scavenges holes or because it is not an efficient proton donor on TiO2 . The results are discussed in light of previously suggested reaction mechanisms for photocatalytic CO2 reduction. The formation of CH4 from CO2 is likely not a linear sequence of reduction steps but includes oxidative elementary steps. Furthermore, new hypotheses on the origin of the required protons are suggested. Abstract : Bare TiO2 cannot conduct a photocatalytic oxidation reaction and photocatalytic CO2 reduction simultaneously, as demonstrated by Moustakas et al. This points to a key role of holes in the CO2 reduction mechanism towards the final product CH4 .